On the Feminist Thought and Science - Arrieta de Guzmán, Teresa (2018)
This article deals with the relationship between feminism and science. First, we will offer a panoramic view of the various positions regar- ding feminist thought and its contribution to the fields of the Theory of Knowledge and the Philosophy of Science; we will present the doctrines of Sandra Harding and Susan Haack, which show the polarization bet- ween positions that totally reject the conception and practice of past and present science, considering it absolutely androcentric, in front of those who maintain that science has nothing to do with gender, therefore the only idea of a feminist epistemology is incongruent. Then, finally, we will make an analysis of the above, reaffirming concepts that we consi- der realistic and rejecting those we deem erroneous or exaggerated, to reach our own conclusions, emphasizing the importance of not overloo- king points of view traditionally considered marginal.